The impact of planning and communication on unplanned costs in surgical episodes of care: Implications for reducing waste in hospital operating rooms - Dreyfus, David; Nair, Anand; Rosales, Claudia (Journal of Operations Management, 2020)
AbstractThis ethnographic study of more than 90 surgeries (referred to as episodes of care) identifies the antecedents to operating room (OR) supply waste. The study specifically considers the role of planning instances and communication patterns among members of the surgery team on supply waste within the OR. We operationalize planning instances in terms of the number of changes to the physician preference card (PPC), the key document that is used to plan items needed for surgery. Communication patterns among members of the surgery team are captured by measuring the density of communication among the OR team members during an episode of care. The unplanned costs during an episode of care are used as a measure of OR supply waste. Hundreds of hours were spent observing episodes of care and tracking supplies. A combination of participant‐observation, survey, and secondary data were analyzed to extract theoretical and practical insights. The results show that planning instances have a curvilinear relationship with unplanned costs. In particular, as the number of changes to the PPC increases, unplanned costs first increase and then decrease. Higher density of the OR team's communication network is associated with lower unplanned costs. This study has significant theoretical and managerial implications that we discuss and offer directions for future research.